Hubungan Sikap dan Tingkat Aktivitas Fisik dengan Kejadian Noncommunicable Disease pada Tenaga Pendidik dan Tenaga Kependidikan di SMAN 15 Medan: Penelitian - Lorensia Eninta; Alam Bakti; Taufik Ashar; Kintoko Rochadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the relationship of attitudes and physical activity levels with the incidence of noncommunicable diseases in educators and educational staff at SMAN 15 Medan. This type of research uses quantitative research with a Cross Sectional approach. The sampling technique in this study used total sampling, the number of samples was 90 respondents. Data analysis using univariate analysis and bivariate analysis using chi-square statistical test. The results of this study indicate that there is a relationship between age and the incidence of noncommunicable disease in educators and education staff at SMAN 15 Medan with a ρ-value = 0.001, there is no relationship between gender and the incidence of noncommunicable disease in educators and educational staff at SMAN 15 Medan with a p-value = 0, 274, there was no relationship between attitude and the incidence of noncommunicable disease in educators and educational staff at SMAN 15 Medan with p-value = 0.552, there was no relationship between physical activity level and the incidence of noncommunicable disease in educators and educational staff at SMAN 15 Medan with p-value = 0.922.